A Clinical Case of Out-of-Hospital Cardiac Arrest and Post-Resuscitation Disease in a Patient with Acute Myocardial Infarction - Andriy P. Mazur; Elina I. Novikova; Natalia O. Kuzminova (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Prediction of survival in adult patients after out-of-hospital cardiopulmonary resuscitation remains a difficult issue. This clinical case describes our experience of managing a patient after an out-of-hospital cardiac arrest due to an acute coronary syndrome with the development of postanoxic coma, with subsequent successful restoration of neurological function.Case description. Patient K., a 48-year-old man, was delivered unconscious (Glasgow Coma Scale score 7) without spontaneous breathing. During transportation to the hospital, ventricular fibrillation occurred, cardiopulmonary resuscitation lasting 1 hour was performed with restoration of sinus rhythm. Diagnosis: acute coronary syndrome with ST segment elevation; cardiogenic shock; condition after cardiopulmonary resuscitation. Stenting of the occluded circumflex artery was performed. During the patient’s stay in the intensive care unit (ICU), hemodynamics and laboratory tests were carefully monitored and no significant systemic disorders were detected. The patient stayed in the ICU for 19 days. At the time of discharge, the general condition was relatively satisfactory, Glasgow Coma Scale score was 14-15, with minimal neurological deficit. The patient was transferred to a neurological department for further rehabilitation.Results. Determining the probability of either good or bad outcome in comatose patients after cardiac arrest is one of the most important steps in treatment after stabilization of the heart activity. Recent data confirm the utility of electroencephalography (EEG) monitoring for prognosis. The pattern of response to sedative drugs may provide prognostic information. In this clinical case, when EEG was recorded during sedation, preservation of the response to stimuli was registered, and 48 hours after disconnection, patterns corresponding to awakening were registered, which was considered as a positive prognostic sign.Conclusions. In adult patients after cardiopulmonary resuscitation with postanoxic coma, clinical, neurophysiological and radiological tests predict poor neurologic outcome within the first week after cardiac arrest with a certain percentage of false positive rate. However, most predictors have low sensitivity and specificity. Accurate prognosing requires a comprehensive approach. Neurological examination remains the gold standard, but its result is affected by the effect of sedative drugs used in critical patients in the ICU. The use of EEG increases the accuracy of the prognosing.